A SIMPLE SETUP TO OBTAIN FERROELECTRIC THIN FILMS BY DIP-COATING. - MORENO-CRESPO, C. E.; PELAIZ-BARRANCO, A.; SANTANA-GIL, A.; MéNDEZ-GONZáLEZ, Y.; GUERRA, J. D. S.; GONZáLEZ-ABREU, Y.; SAINT-GREGOIRE, P.; GARCíA-ZALDIVAR, O.; CALDERóN-PINAR, F. (Revista Cubana de Física, 2016)
An easy, home-made experimental setup is presented to process ferroelectric thin films by using the dip-coating method. It has been used a stepper motor, a control circuit that provides electrical power to the motor, and a computer. A LabVIEW program has been developed to control all the process, including the velocities and times for the substrate's movement, which can be selected by the user. This setup allows the preparation of thin films under the same conditions than that of commercial equipment. Thin films from two systems have been obtained, SrBaBiNbO and (PbLa)(ZrTi)O. The corresponding structural and ferroelectric characterizations validate the experimental setup.